A REVIEW OF WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY - Nor Maslia binti Rasli Samudin; Nur Syaza Syamirah binti Azman; Mimi NurBalqis binti Noor Azmi; Rose Bathrisyia binti Mohd Rizal; Irdina Umairah binti Faizal (International Journal of Accounting, Finance and Business, 2022)
The most important factor affecting employee productivity is the workplaceenvironment. Employee productivity, performance, health and safety, comfort, concentration,job satisfaction, and morale are all affected by the physical characteristics of the workplaceenvironment. Workplace motivation is necessary, but the most important factor is internalmotivation, which stimulates employees' desire to work hard and enthusiastically in order toincrease production. When a person can carry out their activity optimally, healthily, safely, andcomfortably, the environment is considered to be appropriate. Long-term, an incompatibleenvironment evolves. Furthermore, adverse environmental conditions necessitate more energyand time, which is incompatible with efficient framework systems. This paper aims at presentingthe reviews of the literature on workplace environment and employee productivity. In thisresearch paper the existing literature on the workplace environment in organizations is beingreviewed. The review will give a holistic understanding of the workplace environment andemployee productivity concept for future researchers and aid to identify the research gap.